PENGEMBANGAN ALAT BANTU LATIHAN PASSING UNTUK MENINGKATKAN AKURASI PADA ATLET BASKET KOTA MEDAN - Ramadani, Indi; Supriadi, Amir (Universitas Negeri Medan, 2024)
Development of Passing Aids to Improve Accuracy is a tool in implementing the passing accuracy training program for basketball athletes. This tool can help, provide convenience and efficiency for athletes and coaches, can also provide various forms of training combined with passing or shotting exercises. This tool can also be used for three types of passing, namely, bounce pass, chest pass, and over head pass. This tool can be adjusted according to the athlete's needs when doing the training process. The research method used in this research is the research and development method. The assessment population in this study were 6 experts, namely 2 sports experts, 2 coaches, and 2 media experts. The form of the tool that has been made beforehand is validated by 3 experts, namely 1 sports expert, 1 trainer expert and 1 tool expert. The first trial of using the tool involved 5 basketball athletes and 3 experts, then the results were validated with an average value of 87.14%. While the results of the trial using the second tool involved 5 basketball athletes and 6 experts, then the results have been validated with the average value of the validity of the six being 90.4%. Based on the results of the validation by the six experts, it can be concluded that the development of passing training aids to improve accuracy is already valid and can be used for passing exercises in basketball clubs.